Third Party Conciliation and Trade Union Recognition: Some British Evidence - Beaumont, P. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1982)
The author uses information obtained from the unpublished conciliation records of the ACAS regional office in Scotland to look at some of the potential influences on the likelihood of a trade union successfully obtaining recognition under these provisions. Three sets of influence are applied using correlation analysis.